Spiritual leadership as a model for performance excellence: a study of Baldrige award recipients. Issue 1 (2nd January 2017) - Fry, Louis W.; Latham, John R.; Clinebell, Sharon K.; Krahnke, Keiko
Abstract: Issues regarding workplace spirituality and spiritual leadership have received increased attention in the organizational sciences. The implications of workplace spirituality for leadership theory, research, and practice make this a fast growing area of new research and inquiry by scholars. The purpose of this research was to test a dynamic relationship between the revised spiritual leadership model, consisting of inner life, spiritual leadership (comprised of hope/faith, vision, and altruistic love), spiritual well-being (i.e. a sense of calling and membership), and key organizational outcomes in a sample of Baldrige Performance Excellence Program award recipients. With structural equation modeling, results revealed a positive and significant relationship between spiritual leadership and several outcomes considered essential for performance excellence, including organizational commitment, unit productivity, and life satisfaction. These relationships were explained or mediated by spiritual well-being. Implications for research and practice are discussed.